Responding to Uncertainty: Teacher Educator Professional Development Through Co-Teaching and Collaborative Reflection (LEARNing Landscapes, 2015)
This exploratory paper describes the collaborative planning, reflection, and teaching for two teacher educators in the process of professional development and acclimation to new faculty positions in a College of Education. As a result of intense and reflective conversations, they discovered a mutual interest in the writings of Schön (1987) and found that his work on uncertainty, uniqueness, and value conflict served as a useful heuristic for understanding their shared experience of co-teaching a curriculum course. Their experiences of reflection in and on action, and their subsequent commitment to changes in their practice as teacher educators, are told in a narrative format to help other college educators see the personal as well as professional growth and development that occurred for both.
Keywords: teacher education; teacher research; co-teaching; collaboration; reflection; practice